The Impact of Calcium Alginate Dressings on Wound Healing in Patients with Diabetic Ulcers - Shadrina, Dhiya; Saputra, Rangga; Aisy, Diah Rihhadatul; Cahyaseno, Dwi Putri; Septiany, Virgenia; Noviasuci, Wulan (Genius Journal, 2026)
Introduction: Diabetic foot ulcers often occur due to a combination of neuropathy (sensory, motor, autonomic) and ischemia. This condition is further exacerbated by infection which generally requires proper care for wound healing. Calcium Alginate Dressing is a group of exudate and odor-absorbent dressings that aim to accelerate the healing process of diabetic mellitus wounds, this support material is made from seaweed with hemostatic properties. Objective: To determine the effect of using calcium alginate dressings in the healing process of diabetic ulcer wounds. Method: This study used a literature review method by searching for articles in the Google Scholar, PubMed, and Research Gate databases with a publication range of 2015-2025. Of the 18 articles found, 8 articles met the inclusion criteria. Result: The use of calcium alginate has been shown to have an effect on diabetic wound healing by creating a moist and protected wound environment, which reduces the risk of infection and improves patient comfort. Conclusion: Calcium alginate creates a moist wound environment, facilitates keratinocyte proliferation and epithelial cell migration, which supports the epithelialization process. The use of calcium alginate as a wound dressing in diabetic wounds provides significant results in accelerating the healing process.